Infuence of Self-Creativity and Social Media Use on Digital Entrepreneurial Intention among Students at the University of Lampung - Putri Adinda Miranti; Aida Sari; Mudji Rachmat Ramelan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Lampung University aims to produce high-quality, competitive graduates who are quickly absorbed by the labor market or become entrepreneurs, in line with its motto